Acute kidney injury in dogs and cats 1. Pathogenesis and diagnosis. Issue 5 (10th May 2013) - Mugford, Adam; Li, Ronald; Humm, Karen
Abstract : Acute kidney injury (AKI), an abrupt loss of renal function, is a commonly encountered emergency in small animal practice. This article, the first of two on AKI, reviews the pathophysiology and diagnosis of the condition in dogs and cats. The second article, to be published in the June issue of In Practice, will cover the treatment, recovery and prognosis associated with AKI.